PENARIKAN TANAH WAKAF PERSPEKTIF HUKUM FIKIH DAN KOMPILASI HUKUM ISLAM - Syaibani, Muhammad; Norlaila Hayati, Anisah (MAQASHIDUNA: JURNAL HUKUM KELUARGA ISLAM, 2024)
AbstractThis research discusses "Withdrawal of Waqf Land from the Legal Perspective of Jurisprudence and Compilation of Islamic Law. The formulation of the problem in this research is how the legal review of Fiqh and the Compilation of Islamic Law (KHI) regarding the withdrawal of the waqf land from the Miftahul Iman mosque and what the status of the waqf land is, as well as what are the reasons that led to the withdrawal of the waqf land from the Miftahul Iman mosque by the wakif (who donated it). Based on the problem formulation, the aim of this research is to determine the legal review of Islamic Jurisprudence and the Compilation of Islamic Law (KHI) regarding the withdrawal of waqf land and the status of the waqf land of the Miftahul Iman mosque, as well as to determine the causes of the withdrawal of the waqf land of the Miftahul Iman mosque by the wakif.This research is classified as a type of empirical research with the approach used, namely the empirical juridical method. The primary data sources in this research are the results of interviews and secondary data are books of Islamic jurisprudence and compilations of Islamic law. Meanwhile, data processing techniques begin with data collection, data reduction, data presentation, analysis and verification. If everything has been done perfectly, then finally conclusions can be drawn from the research.Based on the research results, it is known that the law regarding the withdrawal of waqf land from the Miftahul Iman Mosque carried out by the wakif in terms of the laws of Jurisprudence and the Compilation of Islamic Law (KHI) is haram, because the waqf property is permanent or eternal and becomes the property of Allah SWT. So it cannot be taken back. As for the status of the waqf land at the Miftahul Iman mosque, in terms of Islamic jurisprudence, it has legally become waqf property, because it has fulfilled all the pillars and requirements of waqf implementation, however, if viewed from the Compilation of Islamic Law (KHI), the status of the waqf implementation carried out at the Miftahul Iman mosque is still unclear. , because it has not been registered with the Office of Religious Affairs (KUA)/Official for Making Waqf Pledge Deeds (PPAIW), so there is no written evidence to use as collateral. The main reason for the withdrawal of waqf land was because the wakif was no longer involved in managing the mosque.Keywords: Waqf, Legal Review, Withdrawal of Waqf AbstrakPenelitian ini membahas tentang “Penarikan Tanah Wakaf Perspektif Hukum Fikih dan Kompilasi Hukum Islam. Rumusan masalah dalam penelitian ini adalah bagaimana tinjauan hukum Fikih dan Kompilasi Hukum Islam (KHI) terhadap penarikan tanah wakaf masjid Miftahul Iman dan bagaimana status tanah wakafnya, serta apa alasan yang menyebabkan terjadinya penarikan tanah wakaf masjid Miftahul Iman oleh wakif (yang mewakafkan). Berdasarkan rumusan masalah tersebut, maka tujuan penelitian ini adalah untuk mengetahui tinjauan hukum Fikih dan Kompilasi Hukum Islam (KHI) terhadap penarikan tanah wakaf dan status tanah wakaf masjid Miftahul Iman, serta untuk mengetahui penyebab terjadinya penarikan tanah wakaf masjid Miftahul Iman oleh wakif.Penelitian ini tergolong jenis penelitian empiris dengan metode pendekatan yang digunakan, yaitu metode yuridis empiris. Sember data primer dalam penelitian ini adalah hasil wawancara serta data sekunder adalah kitab fikih-fikih dan kompilasi hukum Islam. Sedangkan teknik pengolahan data diawali dengan pengumpulan data, reduksi data, penyajian data, analisis, serta verfikasi. Jika semuanya sudah dilakukan dengan sempurna, maka terakhir bisa diambil kesimpulan dari penelitian.Berdasarkan hasil penelitian diketahui bahwa hukum penarikan tanah wakaf masjid Miftahul Iman yang dilakukan oleh wakif ditinjau dari hukum Fikih dan Kompilasi Hukum Islam (KHI) adalah haram, karena harta wakaf adalah permanen atau abadi yang beralih menjadi milik Allah Swt. Sehingga tidak bisa ditarik kembali. Adapun status tanah wakaf masjid Miftahul Iman ditinjau dari hukum Fikih telah sah menjadi harta wakaf, karena sudah memenuhi semua rukun dan syarat dari pelaksanaan wakaf, namun jika ditinjau dari Kompilasi Hukum Islam (KHI) pelaksanaan wakaf yang dilakukan di masjid Miftahul Iman statusnya masih belum jelas, karena belum didaftarkan ke Kantor Urusan Agama (KUA)/Pejabat Pembuat Akta Ikrar Wakaf (PPAIW), sehingga belum mempunyai bukti tertulis untuk dijadikan jaminan. Adapun penyebab utama terjadinya penarikan tanah wakaf tersebut, karena wakif tidak dilibatkan lagi dalam kepengurusan masjid.Kata Kunci: Wakaf, Tinjauan Hukum, Penarikan Wakaf